2022
DOI: 10.1055/a-1785-8616
|View full text |Cite
|
Sign up to set email alerts
|

Resection depth for small colorectal polyps comparing cold snare polypectomy, hot snare polypectomy and underwater endoscopic mucosal resection

Abstract: Background and study aims Small colorectal polyps are removed by various methods, including cold snare polypectomy (CSP), hot snare polypectomy (HSP), and underwater endoscopic mucosal resection (UEMR), but the indications for using these methods are unclear. We retrospectively assessed the efficacy of CSP, HSP, and UEMR for small polyps, focusing on the depth of the resected specimens. Patients and methods Outpatients with non-pedunculated small polyps (endoscopically diagnosed as 6 to 9 mm), resect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…This indicates that UEMR has superior vertical resectability. Our findings mirror a previous report in colorectal polyps demonstrating that CSP results in shallower resection depth than hot snare polypectomy or UEMR (35,36). Moreover, the median thickness of the submucosal layer in the UEMR group (546 μm) is highly indicative of sufficient resectability given the definitions of submucosal deep invasion for other gastrointestinal carcinomas (esophagus 200 μm, stomach 500 μm, and colon 1,000 μm).…”
Section: Discussionsupporting
confidence: 91%
“…This indicates that UEMR has superior vertical resectability. Our findings mirror a previous report in colorectal polyps demonstrating that CSP results in shallower resection depth than hot snare polypectomy or UEMR (35,36). Moreover, the median thickness of the submucosal layer in the UEMR group (546 μm) is highly indicative of sufficient resectability given the definitions of submucosal deep invasion for other gastrointestinal carcinomas (esophagus 200 μm, stomach 500 μm, and colon 1,000 μm).…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, there is an ongoing debate regarding the predictability of muscularis mucosa resection. Previously published studies observed that muscularis mucosa was absent in 27.8% of excision specimens, while its presence ranged from 57-92%, even in cases involving cold snare polypectomy with submucosal injection [ 24 - 27 ]. The COLDWATER study revealed a significantly higher muscularis mucosa resection rate for UCSP (UCSP: 81.72±62.81%, CCSP: 72.33± 22.33%, P=0.003), suggesting a more favorable efficacy profile.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of submucosa has been observed in 9-24% of resected specimens following CCSP [ 24 , 26 , 30 ]. However, our study revealed a superficial depth of excision, with only 16.6% and 12.5% of specimens including submucosa in UCSP and CCSP (P=0.25), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Some endoscopists may have difficulty achieving universal cold snare resection of polyps ≤10 mm in size, but we have demonstrated the potential benefit achievable by striving for universal cold snare resection of polyps ≤10 mm. We note cold snaring is inappropriate when endoscopic inspection leads to cancer suspicion, because cold snaring cuts superficially compared with hot snaring [14,15,16]. We previously demonstrated extremely low invasive cancer risk in lesions ≤10 mm [17], and there were no invasive cancers ▶ Table 3 Fraction of patients with various different size polyps and managed entirely by cold snaring in the different size groups, by indication.…”
Section: Discussionmentioning
confidence: 99%